Perancangan Dan Pembuatan Alat Pengering Kerupuk Otomatis Menggunakan Mikrokontroler atmega16 - Elwin Mulyanah; Corie Mei Hellyana - AMIK BSI Purwokerto (Universitas Bina Sarana Informatika, 2015)
Abstract - Kerupuk is a typical Indonesian snack favored by the entire community. In the process of making kerupuk and the most important thing to consider is the drying process. The drying process is still used is the conventional way, using sunlight. However, if the sun does not shine with sunlight or even rain will affect the quality of the kerupuk itself. Therefore, with the advancement of technology in the field of robotics is made drier kerupuk using atmega16. The main components in these tools is the microcontroller as processing input from a light sensor and output the water in the buzer, a heating element and a DC motor. Water sensors will be detected when the weather is cloudy and rainy while, the light sensor will be detected when there is sunlight. When rain and overcast box will come in and when the weather is hot box will come out. Drying with this tool will be more convenient and because the box will automatically move itself in accordance sensor detected.Keywords: tools drying, water sensor, light sensor Abstract - Crackers is a typical Indonesian snack favored by the entire community. In the process of making the crackers and the most important thing to Consider is the drying process. The drying process is still used is the conventional way, using sunlight. However, if the sun does not shine with sunlight or even rain will Affect the quality of the cracker itself. Therefore, with the advancement of technology in the field of robotics is made drier crackers using atmega16. The main components In These tools is the microcontroller as processing input from a light sensor and outputs the water in the buzer, a heating element and a DC motors. Water sensors will be detected when the weather is cloudy and rainy while, the light sensor will be detected when there is sunlight. When rain and overcast box will come in and when the weather is hot box will come out. Drying with this tool will be more convenient and Because The box will automatically move itself in accordance sensor detected. Keywords: tools drying, water sensor, light sensor